1989
DOI: 10.1099/0022-1317-70-3-769
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Transcription Initiation in the Panolis flammea Nuclear Polyhedrosis Virus Polyhedrin Gene

Abstract: SUMMARYThe nucleotide sequence of the polyhedrin gene of Pano/is flammea multiple nucleocapsid polyhedrosis virus (PfMNPV) has been determined. The coding sequences of this gene shared 82% similarity at the DNA level and 88% similarity at the protein level with the polyhedrin gene from Autographa califomica (Ac) MNPV. A single nucleotide deviation from the consensus transcription initiation sequence for baculovirus very late genes was identified in the PfMNPV polyhedrin gene. RNA was prepared from Mamestra bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…This region of sequence contains the 12 bp consensus sequence found upstream of all sequenced hyper-expressed very late NPV genes; however, as in the polyhedrin genes of PfMNPV(A) and MbMNPV, it is not a perfect match with the consensus proposed by Rohrmann (1986). The initiation sites of polyhedrin mRNA of both PfMNPV(A) (Oakey et al, 1989) and AcMNPV (Howard et al, 1986) lie within this sequence. The size of the polyhedrin mRNA for PfMNPV(B) was determined by Northern blot hybridization to be the same size as the 1.0 kb mRNA reported previously for PfMNPV(A) (Oakey et al, 1989) and significantly smaller than that of AcMNPV, 1.15 to 1-2 kb (data not shown).…”
Section: Short Communicationmentioning
confidence: 94%
See 2 more Smart Citations
“…This region of sequence contains the 12 bp consensus sequence found upstream of all sequenced hyper-expressed very late NPV genes; however, as in the polyhedrin genes of PfMNPV(A) and MbMNPV, it is not a perfect match with the consensus proposed by Rohrmann (1986). The initiation sites of polyhedrin mRNA of both PfMNPV(A) (Oakey et al, 1989) and AcMNPV (Howard et al, 1986) lie within this sequence. The size of the polyhedrin mRNA for PfMNPV(B) was determined by Northern blot hybridization to be the same size as the 1.0 kb mRNA reported previously for PfMNPV(A) (Oakey et al, 1989) and significantly smaller than that of AcMNPV, 1.15 to 1-2 kb (data not shown).…”
Section: Short Communicationmentioning
confidence: 94%
“…The initiation sites of polyhedrin mRNA of both PfMNPV(A) (Oakey et al, 1989) and AcMNPV (Howard et al, 1986) lie within this sequence. The size of the polyhedrin mRNA for PfMNPV(B) was determined by Northern blot hybridization to be the same size as the 1.0 kb mRNA reported previously for PfMNPV(A) (Oakey et al, 1989) and significantly smaller than that of AcMNPV, 1.15 to 1-2 kb (data not shown). When stocks of PfMNPV(A) and PfMNPV(B) were propagated in M. brassicae it was observed that PfMNPV(A) consistently produced higher yields of polyhedra.…”
Section: Short Communicationmentioning
confidence: 94%
See 1 more Smart Citation
“…Databank searches revealed the occurrence of RR1-like sequences upstream of the polyhedrin gene in Mamestra brassicae multicapsid NPV (MbMNPV ; , Panolis flammea multicapsid NPV (PfMNPV ; Oakey et al, 1989) and Orgyia pseudotsugata single nucleocapsid NPV (OpSNPV ; Leisy et al, 1986). The predicted amino acid sequences in these viruses showed homology to the N terminus of RR1 (Fig.…”
Section: Comparison Of Baculoviral Rr1 Proteins With Those From Othermentioning
confidence: 99%
“…AAD00095); ManeNPV, Malacosoma neustria NPV (accession no. AAB31529); MbMNPV, Mamestra brassicae MNPV ; OpMNPV, Orgyia pseudotsugata MNPV (Ahrens et al, 1997); OpSNPV, Orgyia pseudotsugata SNPV (Leisy et al, 1986); PaflMNPV, Panolis flammea MNPV (Oakey et al, 1989); PenuNPV, Perina nuda NPV (Chou et al, 1996); RoMNPV, Rachiplusia ou MNPV (Harrison & Bonning, 1999); SeMNPV, Spodoptera exigua MNPV (IJkel et al, 1999); SfMNPV, Spodoptera frugiperda MNPV (Gonzalez et al, 1989); SpltMNPV, Spodoptera litura MNPV (Pang et al, 2001); ThorMNPV, Thysanoplusia orichalcea MNPV (accession no. AF169480); ThorSNPV, Thysanoplusia orichalcea SNPV (Cheng et al, 1998); TnSNPV, Trichoplusia ni SNPV (Fielding & Davison, 1999); WisiNPV, Wiseana signata NPV (accession no.…”
Section: Comparison Of Romnpv and Acmnpv Orfsmentioning
confidence: 99%